2017
DOI: 10.1016/j.jaci.2016.08.056
|View full text |Cite
|
Sign up to set email alerts
|

IL-1 and IL-36 are dominant cytokines in generalized pustular psoriasis

Abstract: Background Generalized pustular psoriasis (GPP) is a rare, debilitating, and often life-threatening inflammatory disease characterized by episodic infiltration of neutrophils into the skin, pustule development, and systemic inflammation, which can manifest in the presence or absence of chronic plaque psoriasis (PV). Current treatments are unsatisfactory warranting a better understanding of GPP pathogenesis. Objective To understand better the disease mechanism of GPP to allow improved targeted therapies. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
394
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 305 publications
(413 citation statements)
references
References 48 publications
12
394
0
7
Order By: Relevance
“…2), most likely because of lack of N-terminal processing 35 . In agreement with previous findings 25,36 , IL-36 can be activated by proteases that are released by activated neutrophils, including elastase (Supplementary Fig. S7).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…2), most likely because of lack of N-terminal processing 35 . In agreement with previous findings 25,36 , IL-36 can be activated by proteases that are released by activated neutrophils, including elastase (Supplementary Fig. S7).…”
Section: Discussionsupporting
confidence: 93%
“…The expression of IL-36 cytokines is elevated in many inflammatory diseases 22,41 . In particular, high IL-36 as well as mutations in IL-36 signaling components The mean values ± SD of are associated with psoriasis 25,30,[42][43][44][45] . The findings that IL-17A induced the expression of the IL-36 cytokines suggested that these are downstream effectors of IL-17A.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations